Analysis Analysis of the Implementation of Internal Control in Productive Waqf Management (Case Study: Nazir Waqf Mata Air) - Azahra Nur Afifah; Dewi Susilowati; Laeli Budiarti (Faculty of Economics and Business, Jenderal Soedirman University, 2026)
This study aims to analyze the application of COSO-based internal control at Nazir Waqf Mata Air and to identify the obstacles encountered in its implementation. The study uses a qualitative method with a case study approach. Data are collected through in-depth interviews, observation, and documentation. The informants in this study consist of four individuals who are directly involved in managing productive waqf assets at Nazir Waqf Mata Air. The results show that, overall, the implementation of COSO-based internal control at Nazir Waqf Mata Air is carried out effectively. The obstacles encountered in the implementation of internal control are related to limited human resources and the underutilization of technology.